Analisis Sistem Pemasaran Digital Dalam Memasarkan Produk Olahan Udang Vaname Pada Kirana Food Sebagai Binaan Dinas Perikanan Kabupaten Lamongan - Aldo Fikhri Firdaus; Sutrisno Adi Prayitno; Resya Nurdyawati; Arini Roro Anggun Tsalasa (Jurnal Ilmu Pertanian dan Perikanan, 2026)
The fishery processing industry, particularly processed whiteleg shrimp (*Litopenaeus vannamei*) products, has significant potential for development in the domestic market. However, the increasing competition in the processed food industry requires Micro, Small, and Medium Enterprises (MSMEs) to implement effective marketing strategies, one of which is digital marketing. This study aims to analyze the implementation of digital marketing strategies at Kirana Food MSME, Lamongan Regency, in supporting the marketing development of processed whiteleg shrimp products. The research was conducted through direct observation, interviews, and documentation of the marketing activities implemented by the enterprise. The findings indicate that Kirana Food has adopted an integrated marketing strategy that combines conventional and digital channels. Offline distribution is carried out through partnerships with modern retail stores and souvenir centers, while digital marketing utilizes various platforms, including Instagram, TikTok Shop, Shopee, and Facebook. The use of digital media serves not only as a promotional tool but also as a means of communicating with consumers, providing product information, and expanding market reach. Therefore, digital marketing strategies play a significant role in supporting the marketing development of processed whiteleg shrimp products at Kirana Food MSME and enhancing opportunities for market expansion in the digital era.